ANALYSIS COMPARISON NPP THORIUM FUEL AS AN ALTERNATIVE ENERGY SOURCES - Muhammad Rasyid Ridhani; Nofriady Aziz; Kris Tri Basuki (Fakultas Teknik Universitas Wahid Hasyim, 2016)
Electrical energy needs of Indonesia is increasing every year so many power plants being developed to meet the national energy purposes, both of which use fossil fuels, solar, wind and others. One of the sources of energy that has a vital and strategic role to support the resilience of the national electrical energy is nuclear. Besides nuclear energy source that is proven to be safer and environmentally friendly when compared with other types of power plants. Today, it has developed PTLN that uses thorium as a fuel alternative to uranium because thorium is known to have properties superior nuclear and the amount of reserves 3-4 times greater than uranium. The purpose of this research is knowing the advantages of thorium (Th), conducting comparative thorium power plant with other power plants, develop thorium as an alternative energy source. The research method isto comparating power plant in Indonesia.Nuclear power plant with Thorium fuel in 1000 MW have a little amount of Fuel , little Waste, cheap electricity cost (kWh) operation cost and require few area than the other. Keywords : electrical energy, nuclear energy, thorium